Postoperative Rehabilitation and Return-to-Sport Criteria Lack Standardization Following Surgical Repair of Metacarpal Fractures: A Systematic Review - Brian M. Phelps, M.D.; Nikhilesh Mehra, B.S.; Kihoon Bohle, B.S.; Austin Hagen, B.S.; Andrew George, M.D.; Shari R. Liberman, M.D.; Robert A. Jack, II, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To identify any postoperative rehabilitation parameters, as well as return-to-sport criteria after surgically treated fractures of the second through fifth metacarpals. Methods: Level I to IV studies that examined nonthumb metacarpal fractures treated surgically, had a minimum 12-month follow-up, and provided explicit return-to-sport (RTS) criteria were reviewed. The selected studies were evaluated for RTS criteria, RTS outcomes, and methodologic quality. Results: Out of 1,688 studies initially identified, 3 met inclusion criteria. These studies comprised 91 patients from 6 distinct sports. The time frame for RTS varied from 1.8 to 3.4 weeks after surgery. Rehabilitation protocols emphasized range-of-motion exercises and bracing (67%). All studies included a rehabilitation protocol and subjective RTS criteria. However, none suggested specific objective measurement for RTS following metacarpal fracture surgery. Conclusions: In the literature, there is a lack of agreement on the criteria for rehabilitation and returning to sport after surgical repair of metacarpal fractures. Each included study described the use of early ROM progression, and most reported using splint immobilization or bracing when returning to training or play. Subjective parameters for RTS were more widely reported than a specific postoperative amount of time, but these parameters varied based on sport and surgeon preference. Level of Evidence: Level IV, systematic review of Level III to IV studies.